b dvancing children's skills and strategies /c - Wright, Robert J.; Martland, Jim.; Stafford, Ann K.; Stanger, Garry (b, 2006)
Helping teachers identify where their students are in terms of number skills, and setting out a strategy for developing their knowledge, this work shows how to advance children's learning across five stages of early arithmetical learning - emergent, perceptual, figurative, initial number, and facile number
Includes bibliographical references and index.
Keywords: Arithmetic -- Study and teaching (Elementary) -- Activity programs; Numeracy -- Study and teaching (Elementary) -- Activity programs; EDUCATION / Elementary